GESTASYONEL DİABETES MELLİTUS (GDM) TANISI ALAN OLGULARDA PREPTİN, LEPTİN VE İNSÜLİN DİRENCİ ARASINDAKİ İLİŞKİNİN ARAŞTIRILMASI - UNCU, UMUT (Fırat Üniveristesi, 2016)
Amaç: Gestasyonel diyabet ilk kez gebelik sırasında ortaya çıkan glukoz tolerans bozukluğu olarak bilinir. GDM tanısının konması anne ve bebek açısından oldukça önemlidir. Bu çalışmada, insülin ve glukoz metabolizması üzerine etkileri olduğu bilinen Leptin ve preptin testlerinin, GDM tanısı alan gebelerde, insülin direnci ve insülin direnci ile ilgili test parametreleri arasındaki ilişkinin araştırılması amaçlanmıştır. Gereç ve Yöntem: Çalışmamız, gönüllü katılım formunu dolduran gebelerden oluşmaktadır. Bu gebelerden sağlıklı 41 gebe kontrol grubunu, 38 gebe ise GDM tanısı alıp GDM gurubunu oluşturmaktadır. Gebelerin rutin tahlileri için açlık sırasında alınan kan örneklerinden 4mL kadar da aprotininli tüplere alınarak preptin ve leptin parametreleri çalışılmıştır. Bulgular: Çalışmamızda kontrol ve GDM grubu için yaş, VKİ ve ailede diyabet öyküsü faktörleri p<0.05 anlamlılık düzeyine göre anlamlı bulunmuştur. Leptin parametresi p<0.05 anlamlılık düzeyine göre anlamlı bulunurken preptin parametresi anlamlı bulunmamıştır p>0.05. Sonuç: Çalışmamızda elde edilen leptin verileri GDM'li gebelerde p<0.05 anlamlılık düzeyine göre anlamlı bulunmuşken, preptin verilerinde anlamlı bir fark bulunamamıştır p>0.05. Anahtar Kelimeler: Gestasyonel Diabetes Mellitus (GDM), Preptin, Leptin.

Aim: Gestational diabetes is known as the disorder of glucose tolerance which occurs during first pregnancy. GDM diagnosis is crucial for the sake of the baby and the mother. In this work, it is aimed to research the applicability of Leptin and Preptin tests who are known to have an effect on insulin and glucose metabolism on GDM diagnosed pregnant patients, the insulin resistance, the parameters related to it and their correlation. Equipment and Method: Our work consists of volunteers who have filled out the application form. Among those who have volunteered by filling the participation form and became our test subjects, 41 of them form the healthy pregnant control group while 38 of them forms the GDM diagnosed group. From the blood samples taken while the test subject has an empty stomach for routine pregnancy tests, 4mL of the samples has been taken into test tubes with aprotinin and their preption and leptin parameters have been studied. Findings: In our work, for the GDM and control groups, age, BMI and the family's diabetical history factors have been found to be significant according to the p<0.05 significance level. Leptin parameters have been found to be significant according to the p<0.05 significance level while preptin parameters has been found to be insignificant p>0.05. Results: Leptin parameter has been found to be significant in GDM diagnosed pregnant patients according to the p<0.05 significance level while preptin parameters has been found to be insignificant. Keywords: Gestasyonel Diabetes Mellitus (GDM), Preptin, Leptin.
Research of the relation between preptin, leptin and insulin resistance in gestational diabetes mellitus (GDM) diagnosis situations
Keywords: Biyokimya